Learning Power from the Margins: Analyzing Action and Reflection in a Social Movement - Donna M. Chovanec (Adult Education Research Conference, 2004)
In this paper, I apply the notion of praxis, the dynamic interaction of action and reflection needed for social change, to empirical analysis of a defining moment in the Chilean women’s movement.